The Relationship between Sleep Quality and the Incidence of Gastroesophageal Reflux Disease (GERD): A Study on Clinical Clerkship Students, Faculty of Medicine, Universitas Prima Indonesia - Nurhayati; Chairul Radjab Nasution; Fiska Maya Wardhani (Eureka Herba Indonesia, 2023)
Gastroesophageal reflux disease (GERD) is defined as a gastrointestinal motility disorder caused by the reflux of gastric contents into the esophagus or oral cavity. This results in symptoms or complications if persistent, resulting in a significant reduction in quality of life and morbidity. Several studies have reported an association between nocturnal GERD and sleep disturbances, which can significantly affect the quality of life. This study explores the relationship between sleep quality and the incidence of GERD in clinical clerkship students at the Faculty of Medicine, Universitas Prima Indonesia. This study is a cross-sectional observational study involving 144 clinical clerkship students. The GERDQ was used to diagnose GERD, and the PSQI questionnaire was used to measure sleep quality. Respondents who did not suffer from GERD with good sleep quality were 32 respondents (22.2%). Those who did not suffer from GERD with poor sleep quality were 65 respondents (74.8%), who suffered from GERD with good sleep quality only 1 respondent (10, 8), and 46 respondents (36.2%). There is a significant relationship between sleep quality and GERD in clinical clerkship students at the Faculty of Medicine, Universitas Prima Indonesia.